The Influence of Daily Physical Activities on Blood Pressure in Elderly Patients Suffering from Treated Hypertention at Grandmed Hospital, Lubuk Pakam - Sitepu, Sari Desi Esta Ulina; Sipayung, Selamat Tuahta; Hayati, Kardina (JURNAL PENGMAS KESTRA (JPK), 2023)
Hypertention is a type of cardiovascular disease that attacks people, especially the elderly. If you don’t get proper treatment, hypertention causes very serious complications and can even cause loss of life. Handling to reduce hypertention pressure can be done in a non-pharmacological way, namely through physical activity. Doing physical activity is useful for improving blood circulation so that hypertention does not occur. This community service activity is carried out to increase knowledge and train elderly patients who suffer from hypertension to carry out physical activities in daily life to control blood pressure. The community service method is carried out by sending a team to conduct a survey at the hospital and meet directly with patients to conduct an assessment of the condition of elderly people who suffer from hypertension, then developed and plan solutions for handling the problems. Counseling was carried out on the topic of the effect of carrying out physical activity (activities) on blood pressure which was carried out in elderly patients treated at Grandmed Lubuk Pakam Hospital. Physical activities carried out starting from light, moderate and heavy physical activities. The results of the post test conducted through blood pressure examination results in elderly patients showed a decrease in blood pressure that occured after physical activity. This community service activity is expected to be useful and apllied in every life, especially in elderly patients who suffer from hypertension.